A Phase I First-in-Human Study of ABBV-383, a B-Cell Maturation Antigen × CD3 Bispecific T-Cell Redirecting Antibody, in Patients With Relapsed/Refractory Multiple Myeloma. Issue 31 (1st November 2022) - D'Souza, Anita; Shah, Nina; Rodriguez, Cesar; Voorhees, Peter M.; Weisel, Katja; Bueno, Orlando F.; Pothacamury, Rajvineeth K.; Freise, Kevin J.; Yue, Susan; Ross, Jeremy A.; Polepally, Akshanth R.; Talati, Chetasi; et al.
Abstract : PURPOSE: ABBV-383, a B-cell maturation antigen × CD3 T-cell engaging bispecific antibody, has demonstrated promising results in an ongoing first-in-human phase I study (ClinicalTrials.gov identifier: NCT03933735 ) in patients with relapsed/refractory multiple myeloma (RRMM). Herein, we report safety and efficacy outcomes of this phase I dose escalation/expansion study. METHODS: Patients with RRMM (≥ three prior lines including a proteasome inhibitor, an immunomodulatory drug, and an anti-CD38 monoclonal antibody) were eligible. ABBV-383 was administered intravenously over 1-2 hours once every 3 weeks, without any step dosing. A 3 + 3 design with backfilling for dose escalation was used (intrapatient escalation to highest safe dose permitted) followed by initiation of dose expansion. RESULTS: As of January 8, 2022, 124 patients (dose escalation [0.025-120 mg], n = 73; dose expansion [60 mg], n = 51) have received ABBV-383; median age was 68 years (range, 35-92 years). The most common hematologic treatment-emergent adverse events (TEAEs) were neutropenia (all grades: 37%) and anemia (29%). The most common nonhematologic TEAEs were cytokine release syndrome (57%) and fatigue (30%). Seven deaths from TEAEs were reported with all considered unrelated to study drug by the investigator. For all efficacy-evaluable patients (n = 122; all doses), the objective response rate (ORR) was 57% and very good partial response (VGPR) or better (≥ VGPR) rate was 43%. In the 60 mg dose expansion cohort (n = 49), the ORR and ≥ VGPR rates were 59% and 39%, respectively; and in the ≥ 40 mg dose escalation plus dose expansion cohorts (n = 79) were 68% and 54%, respectively. CONCLUSION: ABBV-383 in patients with RRMM was well tolerated with an ORR of 68% at doses ≥ 40 mg. This novel therapy's promising preliminary antitumor activity in heavily pretreated patients warrants further clinical evaluation.